Role of IoT Intelligence System & Big Data Management to Control Flood Data - Anitha, Cuddapah; Tandon, Shalu; Vamsikrishna, M.; M., Arunmozhi; Chauhan, Megha; Bajaj, Ram (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The increasing danger posed by floods requires the development of inventive strategies to ensure efficient management and reduction. This study explores the capacity for integrating Internet of Things (IoT) intelligence technologies and big data management to bring about significant changes in flood control tactics. Examining the interdependent connection between the Internet of Things (IoT) and big data, focusing on their functions in the areas of real-time monitoring, predictive analytics, and response mechanisms. The implementation of IoT sensor networks allows for the collecting of real-time data, while big data analytics enables the extraction of valuable insights from various datasets. The combination of these technologies holds the potential to completely transform flood control, equipping authorities with timely information to make proactive decisions. Nevertheless, the obstacles pertaining to data security, scalability, and standardisation necessitate meticulous deliberation. This paper seeks to examining & exploring the movements & process of using IoT intelligence systems and big data management to regulate flood data by thoroughly analysing case studies and technology applications.